PERANCANGAN KATALOG GALERI PENGANTIN “TITIN DONA” DUMAI - GUSNI WIDIA SARI, Dra. Zubaidah, M.Sn., Dra. Jurpiani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Titin Dona Bridal Gallery is a service business that serves and helps brides a in preparation for weddings and make-up. Titin Dona provides brides fashion models and modern until traditional makeup. Information about Titin Dona bridal Gallery is not optimal because it only displays images of products or services through social media like Facebook and Instagram, for that needed other media as a support to help consumers so that they can increase promotions with catalogs.design method used in this catalog is Glass Box method. Through this method, it can be easy for designers to designing. Then approach the SWOT analysis (Strength, Weakness, Opportunity, Treat). The method is used to evaluate the strengths, weaknesses, opportunities, and threats of Titin Dona who will useful in this design.The orientation of this idea to making the main media in the form of catalogs. It is expected that the presence of catalog be media can give a strength to compete with competitors that have expanded at this time. Catalogs are supported by several media lika a posters, wall clocks, stamps, stickers, x-banners, business cards, notes, mugs and clothes that aim to strengthen the application of the main media.Keywords: Design, Catalog, Promotion, Titin Dona Gallery